Analysis of the Structure of the Existing Administration Building into Two Floors at the Class III Naha Airport Operator Unit, Tahuna - North Sulawesi - Juhal Ramadhan, Olsyah; Fatimah, Siti; Wasito, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The administration building is a land-side facility that aims to organize airport administration and also control services in the airport work environment area. The administration building at Naha Airport needs to be expanded to two floors and improvements to the building construction to improve the safety of the building construction and also the safety of workers. There are several things in this planning, one of which is redesigning plates, beams, and columns. From the results of the analysis, the location of the construction of the administration building is in risk category E so that the structural analysis uses the SRPMK (Special Moment Bearing Frame System) method. In planning the building structure, SNI 2847: 2019 concerning reinforced concrete and SNI 1727: 2018 for loading are used. In this final project, the SAP 2000 auxiliary program is used for 3D building modeling, PCAColumn for calculating column interaction diagrams, and Autocad 2018 for reinforcement details. In this final project, the calculation of the Cost Budget Plan is also needed to determine the estimated cost of rebuilding the administration building into two floors. From the structural design results, the dimensions of the main beam (B1 25/40), child beam (B2 15/30), column (K1 25/25) and plate thickness of 12 cm and structural reinforcement details are included in the engineering drawings. In addition, the design control check of the administration building structure based on SNI 1726: 2019 has met the requirements.